Alteraciones de la forma y la dimensión de las arcadas en niños con dentición decidua completa de 3 a 5 años de la Escuela Marieta de Veintimilla durante el periodo marzo-julio 2015. - Moreno Criollo, Ana Cristina (2016)
This study was done in order to determine the changes in shape and size of the dental arches in children with complete primary dentition, the sample consisted of 50 children corresponding to 25 men and 25 women aged 3-5, who were children that study at “Marieta de Veintemilla” school.In the models the shape of both upper and lower arch was analyzed, through a clinical observation, the results showed that in both arcades the most prevalent shape is the rounded one with a 54% in the upper arcade, and 52 % in the lower arcade. When the upper arch was measured, the dimension of higher prevalence was 68-72 mm with a 60% and in a lower percentage of 76-80 mm with 18%; where as in the lower arch the dimension of higher prevalence was 66-69 mm with a 46%, and in a lower percentage of 61-65 mm 26%. About the symmetry, 80% of children have a symmetric upper arch while 20% do not; and, about the lower arch, 74% of children have symmetric arches and 26% do not. About asymmetries, 20% of children have mandibular asymmetry, 14% maxillary asymmetric and a 6% have mixed asymmetric. Tooth space loss also was measured, and only 4% of children have tooth loss of space and it was in the right mid-arcade; whereas in the lower arch 8% of children have tooth space loss in the right mid-arcade as well. Key words:Shape and dimension, Arcade, Teethingdecidua